Investigating the potential of sunflower species, fermented palm wine and Pleurotus ostreatus for treatment of petroleum-contaminated soil. (February 2020) - Dickson, Udeme John; Coffey, Michael; George Mortimer, Robert John; Smith, Barry; Ray, Nicholas; Di Bonito, Marcello
Abstract: Phyto- and myco-remediation have been identified as sustainable options for treatment of petroleum-contaminated soils. To appraise the benefits thereof, the potentials of 3 sunflower species, 2 palm wine types and P. ostreatus to treat petroleum-contaminated soils was investigated. The study involved sampling of petroleum-contaminated soils and treatment with the phyto- and myco-remediation agents for a period of 90-days. Agents used for the remediation were 3 species of sunflowers ( Helianthus annus -pacino gold, Helianthus sunsation & Helianthus annus -sunny dwarf), fermented palm wine (from 2 species of palm trees - Elaeis guineensis & Raffia africana ), and oyster mushroom ( Pleurotus ostreatus ). The study further investigated variation in remediation efficiency among the sunflower and palm wine species, as well as different substrates and conditions for optimal application of P. ostreatus . The results obtained revealed up to 340 g/kg dry weight of Total petroleum hydrocarbons (TPHs) in the soils, with remediation outcomes of up to 69% by the sunflower- Helianthus annus (Pacino gold), 70% by fermented palm wine, and 85% by P. ostreatus . While the remediation efficiency of sunflower species was proportional to biomass, there was no significant difference in remediation efficiency of the palm wines. It was also found that substrates type and method of application has a significant impact on the remediation efficiency of P. ostreatus. The study further revealed available nitrate and electrical conductivity as possible useful indicators of TPHs concentration and remediation progress in soils. Graphical abstract: Image 1 Highlights: TPHs levels in soils was as much as 339 g/kg dry weight. Remediation efficiency of sunflower species was up to 69%, fermented palm wine-70% and P. ostreatus- 85%. Remediation efficiency of sunflower species was proportional to biomass. Remediation efficiency of P. ostreatus depends on substrates type and method of application. Available nitrate and electrical conductivity are useful indicators of TPHs concentration in soil.